How we study cryptic species and their biological implications: A case study from marine shelled gastropods - Caren P. Shin; Warren D. Allmon (Ecology and Evolution, 2023)
Abstract Methodological and biological considerations are intertwined when studying cryptic species. A potentially large component of modern biodiversity, the frequency of cryptic species among taxonomic groups is not well documented. The term “cryptic species” is imprecisely used in scientific literature, causing ambiguity when interpreting their evolutionary and ecological significance. This study reviews how cryptic species have been defined, discussing implications for taxonomy and biology, and explores these implications with a case study based on recently published literature on extant shelled marine gastropods. Reviewed gastropods were recorded by species. Records of cryptic gastropods were presented by authors with variable levels of confidence but were difficult to disentangle from inherent biases in the study effort. These complexities notwithstanding, most gastropod species discussed were not cryptic. To the degree that this review's sample represents extinct taxa, the results suggest that a high proportion of shelled marine gastropod species are identifiable for study in the fossil record. Much additional work is needed to provide a more adequate understanding of the relative frequency of cryptic species in shelled marine gastropods, which should start with more explicit definitions and targeted case studies.